Upaya Peningkatan Pembuatan Sofa dengan Memperhatikan Value Added dan Value Engineering - Arika, Windy; Murnawan, Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
There is waste in the production process due to losses such as the raw materials for making sofas being much greater than customer demand, sometimes workers or employees make mistakes in the process of making and repairing sofas which results in low customer satisfaction with the quality of sofa products, and price submissions that make customers doubt the offer. the price, then the owner of the UMKM sofa offers the customer to service the sofa to another UMKM sofa to compare the price whether it is lower or higher. The application of value addition and engineering plans can be in the form of improving the production process, using more efficient raw materials, performing sofa models, and efficient production process times. As a result of the application of value added and value engineering that has been carried out, the results of the budget plan are IDR.6,546,000 for the initial sofa product, the 1 design sofa product results in a budget plan of IDR.6,521,000, the 2 design sofa product results in the budget plan the cost